Effects of Bariatric Surgery on the Consumption of Sweets and Fatty Foods by Patients in their Pre and Postoperative Period - Fernandes Dias, Lineker; Clara Toledo Detoni, Ana; Lyssa de Castro Andrade, Giovanna; Vilela Alves, Gustavo; Victor Silveira Machado de Campos, João; Martins Machado Araújo, Jordana (Journal of Health Care, 2021)
INTRODUCTION: Patients undergoing bariatric surgery (CB) report changes in their eating behaviors that may result from behavioral, anatomical and neuro endocrine causes resulting from the impacts of the surgery. However, there is no consensus in the scientific literature on the impacts of CB on eating behaviors associated, specifically, with the consumption of very caloric foods. OBJECTIVES: To analyze the scientific production that discusses the association between consumption of food with high energy density by patients and their respective periods of pre or post-operative of the BC. MATERIAL AND METHODS: Integrative literature review carried out in the SciELO, Medline, and Lilacs databases. Data collection took place between March and June 2020. For the analysis of this study, articles published after 2015 with research proposals in line with the objective of this research were considered. RESULTS: The initial sample of articles with the application of the inclusion and exclusion criteria were 114 articles. After selection looking for manuscripts that met the scope of this review, the total number of papers selected to study its content was 34 articles. CONCLUSIONS: The articles indicate that the change in the consumption of sweets and fatty foods in the preoperative period results from behavioral changes aimed at weight loss. However, after CB, the reduction in consumption of these high energy density foods may be associated with intestinal neuroendocrine changes related to satiety, as well as a reduction in the palatability of these food groups.